Albuminuria and other renal damage biomarkers detect acute kidney injury soon after acute ingestion of oxalic acid and potassium permanganate. (15th December 2018) - Wijerathna, Thilini M.; Mohamed, Fahim; Dissanayaka, Dhammika; Gawarammana, Indika; Palangasinghe, Chathura; Shihana, Fathima; Endre, Zoltan; Shahmy, Seyed; Buckley, Nicholas A.
Abstract: Background: Deliberate self-poisoning with a combination washing powder containing oxalic acid (H2 C2 O4 ) and potassium permanganate (KMnO4 ) is a significant medical problem in the Southern Province of Sri Lanka. Acute kidney injury (AKI) is a frequent consequence. Biomarkers for early diagnosis of nephrotoxicity could guide appropriate supportive therapies. Methods: We investigated the performance of three serum biomarkers and nine urinary biomarkers in 85 patients in an ongoing multicenter prospective cohort study in Sri Lanka exploring AKI following poisoning. Results: Sixty two (62/85, 73%) patients developed AKI (acute kidney injury network, AKIN, criteria). Early and rapid increases in serum creatinine (sCr) peaking on day 3 were observed in AKIN stage 2 and 3 patients. In these patients, serum cystatin C (sCysC) rose more gradually but also peaked on day 3. Biomarker concentrations (normalized to urinary creatinine) of urinary albumin (uAlbumin), clusterin (uClusterin), beta-2-microglobulin (uB2M), osteopontin (uOPN), neutrophil gelatinase-associated lipocalin (uNGAL) and kidney injury molecule-1 (uKIM–1) in the AKIN2/3 group increased above the 95th centile concentration of the healthy population. Within 8 h of ingestion, the normalized uAlbumin and sCysC predicted AKIN2/3 with respective area under receiver operating characteristic curve, AUC-ROC values, of 0.94 (95% CI 0.86–1.00) and 0.85 (95% CI 0.76-0.95). Conclusions: Urinary albumin was the best performing AKI biomarker following ingestion of H2 C2 O4 /KMnO4 . This may reflect glomerular injury and/or proximal tubular injury. The urinary albumin concentrations observed in this study could generally be detected using albumin specific dipstick methods, easily available even in resource poor settings.